Recent developments in minimally invasive surgical techniques (Research, Society and Development, 2024)
Despite the undeniable benefits, developments in minimally invasive surgical techniques also face challenges. Issues related to the learning curve for surgeons, costs associated with specialized equipment, and limitations in certain procedures still represent obstacles to be overcome for wider adoption. As research and development continues, new innovations in minimally invasive techniques are expected to continue to shape the future of surgery. Therefore, the objective of this study is to investigate and analyze the most recent developments in minimally invasive surgical techniques, with the purpose of evaluating their effectiveness, safety and impact on clinical practice. Methodology: An integrative review of the literature was carried out, through a survey of data in scientific databases: LILACS, SCIELO and PUBMED. Results and Discussions: In recent years, we have witnessed significant advances in minimally invasive surgical techniques that have redefined the medical landscape. One of the notable innovations was the expansion of the use of robotic surgery, allowing surgeons greater precision and dexterity. Advanced robotic systems, such as the da Vinci Surgical System, have been applied in various specialties, from complex abdominal surgeries to urological and gynecological procedures. Conclusion: In summary, recent developments in minimally invasive surgical techniques represent a remarkable revolution in contemporary medicine. The progressive acceptance and adoption of these approaches by healthcare professionals testifies to the growing confidence in the effectiveness and safety of these innovations.